Association between hypertensive disorders of pregnancy and gestational diabetes and risk of atopic dermatitis in childhood: A systematic review and meta-analysis - Li Pan; Qiuhe Song; Fei Xiong; Fan Hong; Kun Zhu (Elsevier, 2024)
The purpose of this review was to examine if maternal hypertensive disorders of pregnancy (HDP) and gestational diabetes mellitus (GDM) result in an increased risk of atopic dermatitis or eczema (AD-E) in childhood. We searched the databases of PubMed, Embase, CENTRAL, Web of Science, and Scopus for cohort or case-control studies up to 25th June 2023. Random-effects meta-analysis was done to generate the odds ratio (OR) of the association between HDP/GDM and AD-E. Eight studies were included. Meta-analysis of five studies showed that GDM in the mother was associated with an increased risk of AD-E in the offspring (OR: 1.35 95% CI: 1.13, 1.61 I2 = 61%). Pooled analysis of four studies demonstrated no association between HDP and risk of AD-E in the offspring (OR: 1.03 95% CI: 0.99, 1.08 I2 = 0%). The results did not change on sensitivity analysis and subgroup analysis based on study type, method of AD-E diagnosis, and sample size. This meta-analysis suggests that GDM may significantly increase the risk of AD-E in childhood, however, HDP does not seem to impact the risk of AD-E. Evidence is limited by the small number of studies and high interstudy heterogeneity. Further studies are needed to improve the quality of evidence.